Answer:
See below
Step-by-step explanation:
Zeroes
[tex]f(x)=2(x-1)(x+3)[/tex]
[tex]0=2(x-1)(x+3)[/tex]
[tex]0=(x-1)(x+3)[/tex]
[tex]x=1[/tex] and [tex]x=-3[/tex]
[tex](1,0)[/tex] and [tex](-3,0)[/tex]
Axis of Symmetry
[tex]f(x)=2(x-1)(x+3)[/tex]
[tex]y=2(x-1)(x+3)[/tex]
[tex]y=2(x^2+2x-3)[/tex]
[tex]y+2(4)=2(x^2+2x-3+4)[/tex]
[tex]y+8=2(x^2+2x+1)[/tex]
[tex]y+8=2(x+1)^2[/tex]
[tex]y=2(x+1)^2-8[/tex]
[tex]y=a(x-h)^2+k[/tex]
[tex]x=h[/tex]
[tex]x=-1[/tex]
Vertex
[tex]y=a(x-h)^2+k[/tex]
[tex]y=2(x+1)^2-8[/tex]
[tex](h,k)\rightarrow(-1,-8)[/tex]
Y-intercept
[tex]f(x)=2(x-1)(x+3)[/tex]
[tex]f(0)=2(0-1)(0+3)[/tex]
[tex]f(0)=2(-1)(3)[/tex]
[tex]f(0)=-6[/tex]
[tex]y=-6[/tex]
[tex](0,-6)[/tex]
Please review the attached graph for a visual of these key features.